2020
DOI: 10.1039/d0ob01522a
|View full text |Cite
|
Sign up to set email alerts
|

Concise asymmetric synthesis of new enantiomericC-alkyl pyrrolidines acting as pharmacological chaperones against Gaucher disease

Abstract: A concise and asymmetric synthesis of the enantiomeric pyrrolidines 2 and ent-2 are herein reported. Both enantiomers were assessed as β-GCase inhibitors. While compound ent-2 acted as a poor competitive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…To the best of our knowledge, compound 12 represents the first example of a noncompetitive β-Gal inhibitor acting as a pharmacological chaperone on GM1 patients' cells. A chaperoning behaviour for other noncompetitive inhibitors of lysosomal enzymes has been previously observed, in particular for gene mutations leading to Gaucher, Fabry, Pompe, and Tay-Sachs diseases [35].…”
Section: Pharmacological Chaperoning Activitymentioning
confidence: 80%
“…To the best of our knowledge, compound 12 represents the first example of a noncompetitive β-Gal inhibitor acting as a pharmacological chaperone on GM1 patients' cells. A chaperoning behaviour for other noncompetitive inhibitors of lysosomal enzymes has been previously observed, in particular for gene mutations leading to Gaucher, Fabry, Pompe, and Tay-Sachs diseases [35].…”
Section: Pharmacological Chaperoning Activitymentioning
confidence: 80%
“…Compound 35 was the best chaperone candidate, with a GCase rescue similar to that observed with IFG (around 1.5-fold at 5 µM) but at a 10-fold lower concentration (0.5 µM). The presence of the hydroxymethyl moiety in the pyrrolidine skeleton makes an important contribution to glycosidase inhibition [40], but its removal can lead to more hydrophobic compounds that can better cross the cell membranes. Indeed, Castellan et al [41] reported the synthesis of a couple of enantiomeric pyrrolidines, 36 and ent-36 (Figure 10), and their evaluation as GCase inhibitors and activity enhancers in fibroblasts bearing the homozygous N370S mutation.…”
Section: Five-membered Iminosugarsmentioning
confidence: 99%
“…The removal of this group was advantageous for GCase inhibition, as both compounds were more potent inhibitors than the corresponding hydroxymethylated counterparts reported by Kato et The presence of the hydroxymethyl moiety in the pyrrolidine skeleton makes an important contribution to glycosidase inhibition [39], but its removal can lead to more hydrophobic compounds that can better cross the cell membranes. Indeed, Castellan et al [40] reported the synthesis of a couple of enantiomeric pyrrolidines, 36 and ent-36 (Figure 10), and their evaluation as GCase inhibitors and activity enhancers in fibroblasts bearing the homozygous N370S mutation. These compounds can be also considered DAB (21, Figure 8) and LAB (ent-21, Figure 9) analogues, respectively, but lacking the hydroxymethyl moiety.…”
Section: Five-membered Iminosugarsmentioning
confidence: 99%
“…Under this perspective, the L-iminosugar series have also received attention because while D-iminosugars act as competitive inhibitors, the L-enantiomers are often found to be non-competitive inhibitors of GBA. L-iminosugars have proven effective in fibroblasts derived from N370S homozygous GD patients [110]. Non-inhibitory PCs represent a promising option in GD, because many active-site directed molecules failed in clinical trials probably as a consequence of an unfavorable balance between inhibitory versus chaperone behavior.…”
Section: Gaucher Diseasementioning
confidence: 99%